Generation Z's Attitudes Towards Smart Vending Machines At Airports - Melandi Vikarista Luan, Maria; Leli Indratno, Diana; Kuncorowati, Heru (International Journal of Educational Research & Social Sciences, 2025)
This study aims to determine the effect of Perceived Usefulnesss, perceived ease, perceived risk, and generational differences on attitudes towards smart vending machines at the airport. Generational differences are reviewed from generation Z compared to the previous generation, namely the Millennial generation. The study was conducted through a survey of 111 respondents who were taken randomly through accidental sampling, namely those who were intentionally or unintentionally willing to become research respondents. The analysis was conducted using a multiple linear regression approach. The results of the study found that the average attitude of respondents was to like the existence of smart vending machines at the airport. Perception of benefits and perception of convenience have a positive effect on respondents' attitudes towards smart vending machines at the airport, while perception of risk has a negative effect on respondents' attitudes towards smart vending machines at the airport. Generational differences also affect respondents' attitudes towards smart vending machines at the airport. Generation Z has a higher attitude compared to the previous generation (millennials).